Impact of sleep chronotype on blood pressure and metabolic markers - Huang, Weiwei; Wang, Qinglu; Gao, Yuan; Wang, Jiefeng; Wang, Feihao; Tang, Jiyou (Frontiers in Neurology, 2025)
ObjectiveThe aim of this study was to investigate the correlation between sleep chronotype and metabolic markers to further reveal the influence of sleep chronotype on human health.MethodsThe Morningness-Eveningness Questionnaire was administered to 442 volunteers aged 23–70 years old. The sleep chronotype was divided into morning type (167 cases), neither type (224 cases), and evening type (51 cases). Blood pressure was recorded, and fasting venous blood samples were collected to assess liver function, renal function, blood glucose levels, blood lipid profile, and other biochemical parameters.Results1. There was a statistically significant difference in the age of the morning type, neither type, and evening type (p < 0.01), but there was no significant difference in gender, height, weight, and BMI (ps > 0.05). 2. After controlling for the influence of age-related factors, significant differences were seen between morning type, neither type, and evening type groups in creatinine and aspartate aminotransferase (p < 0.05). 3. After controlling for the influence of age-related factors, the evening type group had lower systolic blood pressure, diastolic pressure, and mean arterial pressure (MAP) compared to the morning type and neither type (p < 0.05). 4. After controlling the influence of age-related factors, the MEQ scores were positively correlated with systolic blood pressure, diastolic blood pressure, and mean arterial pressure (r = 0.099, 0.096, 0.104, ps < 0.05).ConclusionThe evening sleep type is more prone to daytime sleepiness. There were significant differences observed in systolic blood pressure, diastolic blood pressure, and MAP. These variations may be linked to the effects of different sleep chronotype on blood pressure regulation or the blood pressure’s autonomous rhythm.